Taking my talents to South Beach (and back) - Stan Veuger; Daniel Shoag (American Enterprise Institute (AEI), 2018)
Veuger and Shoag study the local economic spillovers generated by LeBron James' presence on a team in the National Basketball Association. They trace the impact a star of Mr. James' caliber can have on economic activity by analyzing the impact his departures and arrivals had on business activity close to the Cleveland Cavaliers and Miami Heat stadiums.
Keywords: A; 330; basketball